2016
DOI: 10.1371/journal.pone.0166984
|View full text |Cite
|
Sign up to set email alerts
|

Wdr68 Mediates Dorsal and Ventral Patterning Events for Craniofacial Development

Abstract: Birth defects are among the leading causes of infant mortality and contribute substantially to illness and long-term disability. Defects in Bone Morphogenetic Protein (BMP) signaling are associated with cleft lip/palate. Many craniofacial syndromes are caused by defects in signaling pathways that pattern the cranial neural crest cells (CNCCs) along the dorsal-ventral axis. For example, auriculocondylar syndrome is caused by impaired Endothelin-1 (Edn1) signaling, and Alagille syndrome is caused by defects in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 66 publications
(103 reference statements)
1
20
0
Order By: Relevance
“…Upon more careful analysis, we found that the level of WDR68 is significantly induced in DM (Fig 1A and 1A’, compare lane 3 to lane 1, p<0.05). Consistent with our previous report [23], WDR68 is not detected above background in Δwdr68-9 cells relative to NT1 control cells (Fig 1A and 1A’, compare lane 2 to lane 1 and lane 4 to lane 3, p<0.01). Next, we examined the level of DYRK1A in NT1 control cells and similarly found that the level of DYRK1A is significantly higher in DM than GM (Fig 1A and 1A”, compare lane 3 to lane 1, p<0.01).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Upon more careful analysis, we found that the level of WDR68 is significantly induced in DM (Fig 1A and 1A’, compare lane 3 to lane 1, p<0.05). Consistent with our previous report [23], WDR68 is not detected above background in Δwdr68-9 cells relative to NT1 control cells (Fig 1A and 1A’, compare lane 2 to lane 1 and lane 4 to lane 3, p<0.01). Next, we examined the level of DYRK1A in NT1 control cells and similarly found that the level of DYRK1A is significantly higher in DM than GM (Fig 1A and 1A”, compare lane 3 to lane 1, p<0.01).…”
Section: Resultssupporting
confidence: 93%
“…C2C12 cells grow rapidly when cultured in growth medium (GM), but arrest cellular growth and differentiate into multinucleated myoblasts in low-serum/differentiation medium (DM) [52, 53]. WDR68 is important for this developmental transition [25], and we previously generated Δwdr68 mouse C2C12 sublines and non-targeted (NT1) control cells [23]. Upon more careful analysis, we found that the level of WDR68 is significantly induced in DM (Fig 1A and 1A’, compare lane 3 to lane 1, p<0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations